Evaluation of the Patient Safety Improvement Corps : experiences of the first two groups of trainees - Teleki, Stephanie (Technical report (Rand Corporation) ;, 2006)
The Patient Safety Improvement Corps (PSIC), part of the Agency for Healthcare Research and Quality's (AHRQ's) patient safety initiative, is a program of three one-week sessions (didactic lessons, homework, and a team project) operated collaboratively by the AHRQ and the Veterans' Affairs (VA) National Center for Patient Safety (NCPS). Its purpose is to improve patient safety in the nation by increasing the number and capacity of health care professionals with patient safety knowledge and skills, achieved through training teams from all 50 U.S. states over three years. This report presents findings from RAND's evaluation of the first two years of the PSIC. Data were collected through in-person, group interviews with trainees at the final training session in May 2004 and May 2005, and through individual telephone interviews with the first-year trainees one year later. Overall, reported experiences were positive. Participants valued the broad perspective gained, and the tools and skills they learned and continue to use. They appreciated and continued to draw upon the technical aspects, the hands-on exercises, the knowledge gained through team projects, and the reference materials. Additionally, they value the networking opportunities, and they have made efforts to spread their knowledge. Significantly, there are strong indications that the program has contributed to actions in the field to improve patient safety. Key barriers challenging trainees' program participation and ability to make changes at their home organizations included lack of resources and cultural obstacles (such as blaming individuals for system problems). A need for continued training and programs to train larger, more-diverse teams was also noted. The findings suggest that the PSIC is making important contributions toward building a national infrastructure to support implementation of effective patient safety practices.